Mitochondrial clearance and maturation of autophagosomes are compromised in LRRK2 G2019S familial Parkinson’s disease patient fibroblasts - Korecka, Joanna A (Hum Mol Genet, 2019)
This study utilized human fibroblasts as a preclinical discovery and diagnostic platform for identification of cell biological signatures specific for the LRRK2 G2019S mutation producing Parkinson’s disease (PD). Using live cell imaging with a pH-sensitive Rosella biosensor probe reflecting lysosomal breakdown of mitochondria, mitophagy rates were found to be decreased in fibroblasts carrying the LRRK2 G2019S mutation compared to cells isolated from healthy subject (HS) controls. The mutant LRRK2 increased kinase activity was reduced by pharmacological inhibition and targeted antisense oligonucleotide treatment, which normalized mitophagy rates in the G2019S cells and also increased mitophagy levels in HS cells. Detailed mechanistic analysis showed a reduction of mature autophagosomes in LRRK2 G2019S fibroblasts, which was rescued by LRRK2 specific kinase inhibition. These findings demonstrate an important role for LRRK2 protein in regulation of mitochondrial clearance by the lysosomes, which is hampered in PD with the G2019S mutation. The current results are relevant for cell phenotypic diagnostic approaches and potentially for stratification of PD patients for targeted therapy.